CYBERCRIME AWARENESS AMONG STUDENTS IN JAUNPUR CITY: A COMPARATIVE STUDY - Singh, Radha; Singh, Mili (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The aim of this study is to determine the level of cybercrime awareness among students in Jaunpur region. Technology has become essential in all aspects of life, from household chores to managing multinational companies and ensuring national security. Despite its benefits, technology also poses risks such as fraud, assault, bullying, sexual harassment, and phishing. It is important for students to understand cybersecurity to prevent such crimes. Data was collected from Veer Bahadur Purvanchal University in Jaunpur, Uttar Pradesh using a questionnaire-based survey. Dr. S. Cybercrime Awareness Scale developed by Rajasekhar (2011) measured the awareness of students. The study considered demographic factors such as gender and location to assess the understanding of cyber threats. T-test was used to test the hypotheses. The findings show that there is no significant difference in cybercrime awareness between male and female students, but there is a significant difference between students from rural and urban areas.